Implementasi Layanan Bimbingan Kelompok dengan Teknik Sosiodrama untuk Meningkatkan Kepercayaan Diri pada Siswa SMP di Tana Toraja Kelas VII - Gabriani Paranda; Gita Massora; Dewi Balandatu; Novrianti T. Mindi; Irmani Gelong Pasande (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2026)
This study focused on addressing the problem of low self-confidence among seventh-grade students at SMP In Tana Toraja. The issue was identified through several behaviors, such as difficulty in voicing opinions, lack of courage to stand in front of the class, and minimal participation during the learning process. To address the identified issue, the study was designed to enhance students’ self-confidence through group guidance activities incorporating the sociodrama technique. This investigation adopted a Guidance and Counseling Action Research approach implemented across two consecutive cycles, each involving planning, action implementation, observation, and reflection. The participants consisted of 30 students, while data were collected through questionnaires and observation instruments. The results indicated that students’ self-confidence developed progressively over time. In the initial condition, most students were still classified in the low-confidence category, but improvement began to appear in cycle one and became more significant in cycle two. These changes were reflected in students’ increased confidence in performing, better communication skills, and stronger active participation in group activities. The sociodrama technique provides direct social interaction experiences that help students develop their self-confidence. Based on the results, the use of group counseling activities incorporating sociodrama emerges as a viable strategy for school counselors to support the development of students’ self-confidence.